21st Annual IEEE International Symposium on Personal, Indoor and Mobile Radio Communications 2010
DOI: 10.1109/pimrc.2010.5671804
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum sensing methods for detection of DVB-T signals in AWGN and fading channels

Abstract: Abstract-In this paper, we consider spectrum sensing of DVB-T signals in different fading environments. We compare state-ofthe-art detectors including detectors based on pilot subcarriers, as well as detectors for general OFDM signals that exploit the correlation structure incurred by the cyclic prefix. Energy detection is also included for comparison. We show numerically that the choice of detector depends on the scenario, the detector requirements, and on the available prior knowledge. We also show that it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 9 publications
(20 reference statements)
0
11
0
1
Order By: Relevance
“…It is very important to note that the probability of false detection for the SP-CAF is very small compared to the DVB-T signals detectors presented in [28]. From the above-listed experimental results, it can be concluded that the performance of the SP-CAF detector is efficient for real signals, confirmed by its high detection probability and low probability of false alarm.…”
Section: Scenariomentioning
confidence: 81%
“…It is very important to note that the probability of false detection for the SP-CAF is very small compared to the DVB-T signals detectors presented in [28]. From the above-listed experimental results, it can be concluded that the performance of the SP-CAF detector is efficient for real signals, confirmed by its high detection probability and low probability of false alarm.…”
Section: Scenariomentioning
confidence: 81%
“…This method is simple to implement. The works reported in [10] and [11] are examples of ED implementation for spectrum sensing. Due to its low complexity, energy detection is the most preferable and popular method.…”
Section: Related Workmentioning
confidence: 99%
“…It is considered that PU signal is a deterministic signal, this as sumption is valid for instance in the different standards defined in IEEE 802.22 working groups for Wireless Regional Area Networks (WRAN). As a practical example TV bands digital signals in Advanced Television Systems Committee (ATSC) standards which is used in North America, have predefined features such as the length of PN sequence and pilot symbol and synchronization patterns and thus makes our assumption valid and practical [7]- [10]. In the optimal spectrum sensing, the noise variance at each of the antennas, channel gains and PU signal are known.…”
Section: Basic Assumptions and Op Timal Detectormentioning
confidence: 99%